From ‘cuy' in South America to ‘cavy' in sub-Sahara Africa: Advancing development through South-South Cooperation - Maass, Brigitte L.; Chauca-Francia, L.; Chiuri, Wanjiku L.; Djikeng, Appolinaire; Meutchieye, F.; Pengelly, Bruce C.; Seré Rabé, Carlos (University of Göttingen, 2016)
Neglected and underutilised livestock species like ‘cuy' or ‘domestic cavy' or ‘guinea pig' (Cavia porcellus L.) play an important role in better nutrition and poverty reduction. Cavy is indigenous in South America and has been introduced to sub-Sahara Africa (SSA), where it has an extensive distribution from Senegal in the West to Tanzania in the East. The remarkable adoption by smallholder farmers and peri-urban dwellers of a simple, apparently suitable technology has not received much international attention. Animals mostly roam freely in the kitchen or house and are kept in a way comparable to the traditional one in South America. In SSA, cavies are a source of meat, a flexible source of cash income – particularly used for schooling expenses – and an appreciated source of manure. In many SSA-countries (e.g., Cameroon, DR Congo and Tanzania), predominantly women and teenage boys engage as cavy keepers and sellers in local markets. Keeping cavies is also used as an alternative to consumption of bushmeat in order to protect wildlife in forest zones; or as part of humanitarian starter kits for displaced people in conflict areas. In Peru, improvement programs of ‘cuyes' over the past 60 years have yielded earlier maturing, heavier breeds. Further, improving husbandry and, especially, optimising feeding have led to enhanced ‘cuy' production. In most SSA-countries, however, formal knowledge about optimal cavy husbandry is limited. Production systems are simple and animal mortality seems high, partly a negative consequence of inbreeding. Thus, the animal's potential is not realised, and its consumption is not valued in line with its high nutritional value because of certain cultural perceptions of society. Researchers, development agents, practitioners and donors from sub-Sahara Africa, South America, Europe and Australia have come together to further identify opportunities for advancing the use of this resource through enhanced South-South cooperation. While aiming to understand the multiple roles that cavies can have in enhancing livelihoods, paramount differences in cavy culture between the continents must be recognised. The diverse production realities need to be considered, therefore, by conducting socio-economic, cultural, as well as technological research and development to offer producers an array of suitable options.